OSOBY SAMOTNIE WYCHOWUJĄCE DZIECI DO LAT 18 JAKO SZCZEGÓLNA KATEGORIA BEZROBOTNYCH - Bielak-Jomaa, Edyta (Zeszyty Prawnicze, 2017)
Persons Bringing up Children under 18 Years Alone as a Group of Special Risk on the Labour Market Summary Nowadays the unemployment constitutes one of the most considerable social, economic and political problems. It affects diverse social, age and occupational groups. Nevertheless among the unemployed we can distinguish also those who on account of their life situation were granted a special position, which consequence is ranking them among one of risk groups on the labour market. The situation of certain categories of persons on the labour market is particularly adverse (unfavorable). Certainly, due to difficult personal situation, the persons raising a child alone find themselves in a predicament (plight). On that account state assistance in obtaining employment seems to be indispensable. Persons bringing up alone at least one child under 18 years on account of ranking them among the group of special risk on the labour market are addressees (recipients) of particular services of the labour market. A refund of care costs over a child under 7 years is one of those special solutions. For entitlements of the unemployed raising a child alone a fact that these persons along with the child create the family plays a significant role (is of great importance). One should agree that a single-parent family is in a particular situation, because in this case the burden of its maintenance is on one parent. The support, being aimed at facilitating taking up the employment, for persons raising a child causes no reservations, also in the context of the pro-family policy of the state. Certain doubts referring to character of the suport and his size can however appear (arise). The author of the article makes an attempt to refer to some of doubts.